Customer Shopping Preferences Between Modern Retail Store and Traditional Retail Store in Palangkaraya City - Eghar Lutfian Fahlutvy; I Made Bayu Dirgantara (Enrichment : Journal of Management, 2021)
This study aims to demonstrate the advantages of modern and traditional retailers available to Indonesian consumers especially in the city of Palangkaraya. The research method used is a qualitative method with a phenomenological approach. The reason researchers make phenomenological research more flexible is because they can know more about what factors can influence consumers in choosing retail stores. Data analysis in this study is a qualitative research. The focus of analysis is to elicit the tacit meanings people attach to their actions and responses in relation to a phenomenon. The results showed that the factors that influence consumer buying behavior are: (1) Location factors, (2) Merchandise factors, (3) Price factors, (4) Promotion factors,